Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T19:57:11+01:00
A) 4x- (2x+7) = 4x-2x-7=2x-7
b) 3a-(3a-2)=3a-3a+2=2
c) 2x+ 2y -(x-y)=2x+2y-x+y=x+3y
d)3b-(-9-b)=3b+9+b=4b+9
e)(6a+3b)- (12a+5b) = 6a+3b-12a-5b=-6a-2b
f) x² +y²+z² -(-x² - y² -z²) = x²+y²+z²+x²+y²+z²=2x²+2y²+2z²
2010-03-17T20:00:56+01:00
A)4x-2x-7=2x-7
b)3a-3a+2=2
c)2x+2y-x+y=x+3y
d)3b+9+b=4b+9
e)6a+3b-12a-5b=-6a-2b
f)x²+y²+z²+z²+y²+x²=2x²+2z²+2y²
2010-03-17T20:01:20+01:00
A)
4x- (2x+7)= 4x-2x-7 = 2x-7
b)
3a-(3a-2)= 3a-3a+2 = 2
c)
2x+ 2y -(x-y)= 2x+2y-x+y = x+3y
d)
3b-(-9-b)= 3b+9+b = 4b+9
e)
(6a+3b)- (12a+5b)= 6a+3b-12a-5b = -6a-2b
f)
x² +y²+z² -(-x² - y² -z²= x²+y²+z²+x²+y²+z² = 2x²+2y²+2z²